Między Wschodem a Zachodem. Inwentarz krzemienny z osady ludności kultury ceramiki wstęgowej rytej na stanowisku Podlesie 6, woj. świętokrzyskie - Przeździecki, Michał; Szubski, Michał; Grabarek, Artur (Folia Praehistorica Posnaniensia, 2020)
Paper presents results of analysis of the assemblage of flint artefacts from the settlement of Linear Pottery culture (LBK) at the site no. 6 in Podlesie, Świętokrzyskie voivodeship. Importance of the site is primarily by its location: on the border of two geographical regions, two geological conditions, two settlement eccentrics of the LBK and two provinces of lithic raw materials. Within the flint assemblage we can distinguish two main classes of lithical artefacts: an internally cohesive collection of 104 obsidian products and a collection of 2069 artefacts made of at least five different types of flint. In the group of siliceous rocks, the most numerous is the Jurassic flint from Cracow area – 53%. Second place in the inventory is occupied by the Światchowski flint, which share reaches the level of 19%. Only slightly smaller are amounts of chocolate flint – 15%.